PARTISIPASI KERJA WANITA MENIKAH DI PROVINSI BANTEN TAHUN 2020 - Sukma Direja (FEB Universitas Sultan Ageng Tirtayasa, 2021)
After marriage, women who already have children and who do not have children spend on average more time outside the workforce than women who are unmarried. This study aims to identify the factors that influence the labor force participation of married women in Banten province. By using the probit model, from this study it can be seen if the labor participation of married women in Banten province is influenced by the age of married women, the age squared of married women, the length of school for married women, the status of married women as head of household, household expenses, the number of household members, the number of boys aged 16 years and over, the number of girls aged between 5-15 years, the education of the married woman's husband and the factor of the location where the married woman lives.